Reading Texts on The Violence of God in The Bible - Gregorius Tri Wardoyo (Jurnal Ledalero, 2021)
Violent texts in the bible both in the Old Testament or in the New Testament, especially in the Old Testament, arise a problem for a potential reader on how to read and understand their message and the theology of the author of the Book. For this reason, biblical scholars try to read it and they propose the way to read such texts, such as to read them in the historical context of the Book itself, and interpret them as a reflection of the author and their experience. This article tries to propose another way to read violent texts, in particularly that involve God as author of violent deeds. The methode of this discussion is exegetical analysis on the texts of the Old Testament, especially on those which narrate the violent deeds of God . The result of the study is the violent deeds of God aim to recreate the creation; that is why such violent texts might be read in the frame of the new creation.Key words: Alkitab, Keluaran, Kekerasan, Allah, Penciptaan (Baru)